Modeling past and future surface mass balance of the Northern Patagonia Icefield. Issue 2 (6th May 2013) - Schaefer, M.; Machguth, H.; Falvey, M.; Casassa, G.
Abstract : [1] Glaciers are strongly retreating and thinning in Patagonia. We present new inferences about the climatic situation and the surface mass balance on the Northern Patagonia Icefield in the past and the future using a combined modeling approach. The simulations are driven by NCAR/NCEP Reanalysis and ECHAM5 data, which were physically downscaled using the Weather Research and Forecasting regional climate model and simple sub‐grid parameterizations. The surface mass balance model was calibrated with geodetic mass balance data of three large non‐calving glaciers and with point mass balance measurements. An increase of accumulation on the Northern Patagonia Icefield was detected from 1990–2011 as compared to 1975–1990. Using geodetic mass balance data, calving losses from the Northern Patagonia Icefield could be inferred, which doubled in 2000–2009 as compared to 1975–2000. The 21st century projection of future mass balance of the Northern Patagonia Icefield shows a strong increase in ablation from 2050 and a reduction of solid precipitation from 2080, both due to higher temperatures. The total mass loss in the 21st century is estimated to be 592±50 Gt with strongly increasing rates towards the end of the century. The prediction of the future mass balance of the Northern Patagonia Icefield includes several additional sources of errors due to uncertainties in the prediction of future climate and due to possible variations in ice dynamics, which might modify the geometry of the icefield and change the rate of mass losses due to calving. Key Points: accumulation increased over the NPI from the 1970/80s to 1990s/2000s calving losses of the NPI increased from 1975‐2000 to 2000‐2009 mass loss from the NPI in the 21st century is predicted to be 617+‐50 Gt